ПЕРЕМЕННОСТЬ КВАЗАРА 3С273 ОТ РАДИО ДО ГАММА-ДИАПАЗОНА ДЛИН ВОЛН ЗА ПЕРИОД 1963 – 2011 ГГ - Вольвач, А. Е.; Кутькин, А. М.; Вольвач, Л. Н.; Ларионов, М. Г. (Одеські астрономічні публікації, 2011)
The results of long term monitoring programs of quasar 3C 273 are collected and analyzed over 1963 – 2011 in wavebands from radio to gamma. Using cross-correlation analysis we found time delays between the variations in radio lightcurves. The time delay-to-frequency dependence was approximated by power-law function and the core shift value in the source was calculated. We also estimated the magnetic field strength in the core at 1 pc: B1=0.5±0.1 G.